2021
DOI: 10.1002/nsg.12150
|View full text |Cite
|
Sign up to set email alerts
|

Ground vulnerability derived from the horizontal‐to‐vertical spectral ratio: Comparison with the damage distribution caused by the 2017 ML 5.4 Pohang earthquake, Korea

Abstract: The city of Pohang in South Korea experienced substantial damage following the M L 5.4 earthquake on 15 November 2017. Damage surveys immediately after the earthquake revealed significant spatial variations in damage intensity across the epicentral area. We collected ambient noise data (three-component seismic data) from 124 locations in Pohang, covering a total area of 17 km × 20 km, and applied the horizontalto-vertical spectral ratio technique to estimate the resonance frequency, amplification factor and vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The ground vulnerability index (K g ), estimated by the amplification factor and fundamental frequency of the HVSR curve, was further proposed by Nakamura (1996Nakamura ( , 1997Nakamura ( , 2019 to evaluate the risk of soil liquefaction. Recent studies have used K g to identify sites that are susceptible to strong ground shaking by assessing the correlations between K g and the distributions of structural damage, liquefaction, and ground amplification effects (or site effects) in regions that have experienced strong ground shaking (e.g., Huang and Tseng 2002;Hardesty et al, 2010;Singh et al, 2017;Farid and Mase 2020;Kang et al, 2021). We also validate the use of HVSR in assessing liquefaction potential based on the case study of the 2017 Pohang earthquake.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The ground vulnerability index (K g ), estimated by the amplification factor and fundamental frequency of the HVSR curve, was further proposed by Nakamura (1996Nakamura ( , 1997Nakamura ( , 2019 to evaluate the risk of soil liquefaction. Recent studies have used K g to identify sites that are susceptible to strong ground shaking by assessing the correlations between K g and the distributions of structural damage, liquefaction, and ground amplification effects (or site effects) in regions that have experienced strong ground shaking (e.g., Huang and Tseng 2002;Hardesty et al, 2010;Singh et al, 2017;Farid and Mase 2020;Kang et al, 2021). We also validate the use of HVSR in assessing liquefaction potential based on the case study of the 2017 Pohang earthquake.…”
Section: Introductionmentioning
confidence: 73%
“…HVSR has been successfully employed in a wide range of geological and environmental settings (e.g. Liu et al, 2014;Picotti et al, 2017;Singh et al, 2017;Mase et al, 2020;Singh et al, 2020;Kang et al, 2021;Mase and Sugianto Refrizon, 2021). The advantages of this technique in real-world applications include its low-cost implementation, non-invasive data collection approach, flexible and straightforward instrumentation requirements, relatively short data collection and processing times, and the generation of results that are easily interpreted.…”
Section: Methods and Data Processingmentioning
confidence: 99%
“…The fragility index has been shown to positively correlate to damage and liquefaction potential in several settings, including Japan, California, and India (Nakamura, 1997;Nakamura et al, 2014;Singh et al, 2017;Nakamura et al, 2014 analysed the correlation between fragility index and liquefaction in Tokyo following the 2011 Mw9.1 Tohoku earthquake and suggested that a fragility index above 12 corresponds to areas with high liquefaction risk. Other studies suggest fragility index values above 10 ( Huang and Tseng, 2002) or 20 (Singh et al, 2017;Kang et al, 2021) are indicative of sites with high liquefaction potential. All our sites with a measurable HVSR peak have a fragility index exceeding 10, with several sites exceeding 100, which may represent a high risk of severe shaking and liquefaction in an earthquake.…”
Section: Site Resonance Frequenciesmentioning
confidence: 98%
“…In various studies, Kg represents the impact of seismic wave propagation in terms of damage to building structures, liquefaction, and local site effects [33][34][35][36][37]. The K g values in the Opak River area range from 0.01 to 20.25 (Fig.…”
Section: Seismic Vulnerability Index (Kg) In the Opak Rivermentioning
confidence: 99%